2016
DOI: 10.1038/srep28876
|View full text |Cite
|
Sign up to set email alerts
|

A clinically authentic mouse model of enterovirus 71 (EV-A71)-induced neurogenic pulmonary oedema

Abstract: Enterovirus 71 (EV-A71) is a neurotropic virus that sporadically causes fatal neurologic illness among infected children. Animal models of EV-A71 infection exist, but they do not recapitulate in animals the spectrum of disease and pathology observed in fatal human cases. Specifically, neurogenic pulmonary oedema (NPE)—the main cause of EV-A71 infection-related mortality—is not observed in any of these models. This limits their utility in understanding viral pathogenesis of neurologic infections. We report the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 57 publications
2
10
0
Order By: Relevance
“…In our study, we found increased lung mass, L m , EG-VEGF and NA in lung lysates, mucus production and erythrocytefilled fluid in the alveolar spaces of mice lungs after infection. These features were similar to previous reports involving EV71 infection-induced pulmonary edema in vivo and human fatal cases [29,31,32]. Interestingly, inflammatory cytokines such as eotaxin-1, eotaxin-2, ICAM-1, IL-7, IL-13 and IL-17 were clearly elevated in lung lysates after EV71 infection, while G-CSF, IFN-γ and IL-10 were drastically decreased.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, we found increased lung mass, L m , EG-VEGF and NA in lung lysates, mucus production and erythrocytefilled fluid in the alveolar spaces of mice lungs after infection. These features were similar to previous reports involving EV71 infection-induced pulmonary edema in vivo and human fatal cases [29,31,32]. Interestingly, inflammatory cytokines such as eotaxin-1, eotaxin-2, ICAM-1, IL-7, IL-13 and IL-17 were clearly elevated in lung lysates after EV71 infection, while G-CSF, IFN-γ and IL-10 were drastically decreased.…”
Section: Discussionsupporting
confidence: 90%
“…Pulmonary edema is mainly responsible for fatal HFMD [3,4], which could be defined as an extra-vascular increasing fluid in the lungs [27]. L m , EG-VEGF and NA are known as the indicators of pulmonary edema [28][29][30]. In our study, we found increased lung mass, L m , EG-VEGF and NA in lung lysates, mucus production and erythrocytefilled fluid in the alveolar spaces of mice lungs after infection.…”
Section: Discussionsupporting
confidence: 57%
“…Animal experiments have indicated that 3-day-old BALB/c mice is high susceptible to ZZ1350 and exhibit a various repertoire of clinical symptoms [ 5 ] ranging from skin lesions to paralysis, ataxia, tremors, acute encephalomyelitis and even respiratory disorders under intracerebral, intramuscular, intraperitoneal inoculation. Unlike other animal models [ 9 , 18 , 19 ], ZZ1350 was directly used to infect neonatal mice without pre-acclimated to mouse or mouse cell lines, making it more clinically relevant. Pathological changes were found in skeletal muscle, heart, skin, spleen and small intestine from infected mice.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested ZZ1350 infection led to pulmonary edema with different degrees. Previous publications also reported pulmonary edema model in neonatal mice via intraperitoneal inoculation using mouse adapted strains [ 19 , 21 ]. Hence, the occurrence of pulmonary edema after infection has nothing to do with inoculation routes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation